La valenza etico-metafisica dell’arte: un confronto tra Heidegger e Jaspers - Pasqualin, Chiara (Scenari, 2021)
The reflection on art and its essence is deeply interwoven with the main issues of both Heidegger’s and Jaspers’ existential-philosophical examinations. The presence of such theoretical interconnection is the consequence of the two philosophers acknowledging that art and its experience are defined by a metaphysical character and an ethical value. In particular, a work of art brings into visibility the dimension of Being – which should not be reduced to the ontic-objective reality – and therefore circumscribes the place of an explicit transcendent movement accomplished by existence. In such dynamics, through which individual conscience is expanded, existence is awakened to realizing itself in a path of authenticity, which is conceived differently by the two authors. The transformative power of art is not only directed to individuals, but also affects the intersubjective dimension: namely, the work of art creates community between individuals who are and strive to be themselves. According to Heidegger, the work of art gathers the so-called “mortals” around the common task of guarding Being; whereas Jaspers sees in artistic creation and fruition the opportunity for a communicative exchange between men of different epochs, faiths and cultures, who are thus encouraged to fulfill reason’s potentiality.